Belleville and Environs: Continuity, Change and the Integration of Town and Country During the 19th Century - Widdis, Randy (Urban History Review / Revue d'histoire urbaine, 1991)
This article suggests that while the economic, political and social context provided by the development of capitalism is the framework for the study of the absorption of semi-autarchic economies and local cultures into increasingly broader regional, national and international systems during the nineteenth century, the concepts of modernization and metropolitanism are spatially over-generalized. While it is true that rural communities and small towns in Upper Canada were integrated right from the beginning into these larger systems of production, they on their own played an essential role in satisfying the need for continuity and community, however defined. Smaller urban centres experiencing stagnation or decline during the period of the "Great Transformation" were not all incipient metropolises; some of these centres continued to depend on the export of staples and developed regional specialization in the development and marketing of these products. This examination of Belleville and its relationship with its hinterland supports the case for a contextual approach to the study of the transformation of rural society with the growth of industrial capitalism.